Human Sigma Optimization: Improving Employee Engagement - ENCE RAMLI ALRASHID (Fakultas Ekonomi & Bisnis Universitas Paramadina, 2019)
Competition in banking industry from year to year increasingly fierce. Small capital banks must open compete with large banks in the same segment. Local banks must compete